Apolipoprotein AIV Requires Cholecystokinin and Vagal Nerves to Suppress Food Intake - Lo, Chunmin C. (Endocrine Society, 2012)
Apolipoprotein AIV (apo AIV) and cholecystokinin (CCK) are gastrointestinal satiation signals that are stimulated by fat consumption. Previous studies have demonstrated that peripheral apo AIV cannot cross the blood-brain barrier. In the present study, we hypothesized that peripheral apo AIV uses a CCK-dependent system and intact vagal nerves to relay its satiation signal to the hindbrain. To test this hypothesis, CCK-knockout (CCK-KO) mice and Long-Evan rats that had undergone subdiaphragmatic vagal deafferentation (SDA) were used. Intraperitoneal administration of apo AIV at 100 or 200 μg/kg suppressed food intake of wild-type (WT) mice at 30, 60, and 90 min. In contrast, the same dose did not reduce food intake in the CCK-KO mice. Blockade of the CCK 1 receptor by lorglumide, a CCK 1 receptor antagonist, attenuated apo AIV-induced satiation. Apo AIV at 100 μg/kg reduced food intake in SHAM rats but not in SDA rats. Furthermore, apo AIV elicited an increase in c-Fos-positive cells in the nucleus of the solitary tract (NTS), area postrema, dorsal motor nucleus of the vagus, and adjacent areas of WT mice but elicited only an attenuated increase in these same regions in CCK-KO mice. Apo AIV-induced c-Fos positive cells in the NTS and area postrema of WT mice were reduced by lorglumide. Lastly, apo AIV increased c-Fos positive cells in the NTS of SHAM rats but not in SDA rats. These observations imply that peripheral apo AIV requires an intact CCK system and vagal afferents to activate neurons in the hindbrain to reduce food intake.